EFEKTIVITAS TERAPI MENIUP BALING-BALING TERHADAP SKALA NYERI SAAT DILAKUKAN TINDAKAN INVASIF (INJEKSI) PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) DIRUANG KEMUNING RSUD BAYU ASIH PURWAKARTA - Wirdan Fauzi Rahman,; Serly, Serly; Tabitha Amelia, (Journal of Innovation Research and Knowledge, 2025)
Pain is an unpleasant experience that often causes fear and anxiety in children, especially during invasive procedures such as injections. One non-pharmacological intervention to reduce pain is the pinwheel blowing therapy, which serves as a distraction by shifting the child’s focus to a pleasant activity. Objective: To determine the effect of pinwheel blowing therapy on pain scale during injection procedures among preschool-aged children (3–6 years old) in Kemuning Ward, Bayu Asih Hospital, Purwakarta. This study used a quasi-experimental design with a one-group pretest–posttest design. A total of 30 preschool children undergoing injection procedures were selected using purposive sampling. Pain level was measured using the Wong-Baker Faces Pain Rating Scale. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The mean pain score before the intervention was 5.9, which decreased to 2.3 after the pinwheel blowing therapy. The Wilcoxon test showed a p-value = 0.000 (p < 0.05), indicating a significant difference in pain levels before and after the intervention. Conclusion: Pinwheel blowing therapy was effective in reducing pain intensity during injection procedures among preschool-aged children. This therapy can be applied as a simple, safe, and enjoyable non-pharmacological nursing intervention to minimize procedural pain in children.